An empirically grounded sociotechnical perspective on designing virtual agents for older adults. (1st November 2020) - Sin, Jaisie; Munteanu, Cosmin
ABSTRACT: Autonomous, intelligent virtual agents (IVAs) are increasingly used commercially in essential information spaces such as healthcare. Existing IVA research has focused on microscale interaction patterns, for example those related to the usability of artificial intelligence systems. However, the sociotechnical patterns of users' information practices and their relationship with the design and adoption of IVAs have been largely understudied, especially when it comes to older adults, who stand to benefit greatly from IVAs. Yet, exposing such patterns may more meaningfully relate sociotechnical considerations to users' perceptions and attitudes toward the adoption of emerging technologies such as IVAs. We explore here the feasibility of information models in informing our understanding of how older adults may use and perceive an IVA. To do this, we relate the insights and findings from a case study of health information IVAs to the six stages of the information search process model (ISP). By doing this, we uncover sociotechnical issues pertinent to each stage of the ISP which help to better contextualize (older) users' interaction with intelligent interfaces such as IVAs. Through this, we argue for the potential of information models to inform the design of interactive user interfaces from a sociotechnical approach.